HUBUNGAN POLA ASUH OTORITER ORANG TUA DENGAN MINAT BELAJAR SISWA KELAS VIII MTs. DARUL ILMI TAHUN AJARAN 2021/2022 - Dinda Aulia Putri; Dina Hidayati Hutasuhut (Sekolah Tinggi Pariwisata Mataram, 2022)
Parents have a responsibility towards their children in terms of education. Parents' attention both in terms of morals and material is one of the factors that foster children's enthusiasm for learning. Darul Ilmi Academic Year 2021-2022. The method in this research is quantitative with a correlation approach. The population in this study were Class VIII MTs students. Darul Ilmi Academic Year 2021-2022, totaling 118 students, and the sampling technique in this study was the purposive sampling technique. Researchers use this technique because researchers want to determine students who get authoritarian parenting from their parents. Researchers can determine the sample that gets authoritarian parenting from their parents is by distributing a valid authoritarian parenting questionnaire. The data collection instrument used in this study was a questionnaire. The questionnaire has been tested for validity and reliability, with the results of 36 valid questionnaires on authoritarian parenting questionnaires and 35 valid questionnaires on learning interest questionnaires. The correlation test technique using the product moment correlation formula, from the calculation results obtained a correlation coefficient between authoritarian parenting (X) and learning interest (Y) of rcount = 0.721 > rtable = 0.250. In accordance with the interpretation of the product moment correlation index, this number indicates a relationship between the two variables. The results of this test state that there is a significant relationship between authoritarian parenting and learning interest of Class VIII MTs students. Darul Ilmi Academic Year 2021-2022.